Preferred and actual mode of delivery in relation to fear of childbirth - Anne-Marie Sluijs; Klaas Wijma; Marc P. H. D. Cleiren; Jan M. M. van Lith; Barbro Wijma (Taylor & Francis Group, 2020)
Purpose This prospective cohort study aimed to investigate the interrelation between preferred/actual mode of delivery and pre- and postpartum fear of childbirth (FOC). Material and methods Participants from 13 midwifery practices and four hospitals in Southwest Netherlands filled out questionnaires at 30 weeks' gestation (n = 561) and two months postpartum (n = 463), including questions on preferred mode of delivery, the Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ) and Hospital Anxiety Depression Scale (HADS). Results were related to obstetric data. Results Both severe FOC (OR 7.0, p < .001) and previous Cesarean section (CS) (OR 16.6, p < .001) predicted preference for CS. Severe prepartum FOC also predicted actual CS. Preferring a vaginal delivery (VD) and actually having a CS predicted higher postpartum W-DEQ scores (partial r = 0.107, p < .05). Other significant predictors for high postpartum W-DEQ scores were high prepartum W-DEQ (partial r = 0.357) and HADS anxiety scores (partial r = 0.143) and the newborn in need of medical assistance (partial r = −0.169). Conclusions Women preferring a VD but ending up with a CS are at risk for severe FOC postpartum, while the same risk was not demonstrated for women who preferred a CS but had a VD. Prepartum FOC is strongly associated with postpartum FOC, regardless of congruence between preferred and actual mode of delivery.